2021
DOI: 10.1007/s13311-020-00990-8
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Embolization Device for Intracranial Aneurysms in a Large Chinese Cohort: Complication Risk Factor Analysis

Abstract: During intracranial aneurysm embolization with the Pipeline embolization device (PED), ischemic and hemorrhagic complications have been observed in cases among Western populations. The postmarket multicenter registry study on the embolization of intracranial aneurysms with the PED in China, i.e., the PLUS study, was performed to assess real-world predictors of complications and functional outcomes in patients treated with the PED in a Chinese population. All patients with intracranial aneurysms who underwent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 30 publications
2
24
0
1
Order By: Relevance
“…Since the development of flow diverter stents, they have been used to redirect flow in fusiform aneurysms to achieve high occlusion rates with low rates of recurrence. However, a potential complication of flow diverter use in the posterior circulation is devastating brainstem stroke from occlusion or stenosis of a critical arterial branch ( 19 , 20 ). Our study directly compared complications and clinical and angiographic outcomes between flow diverter and conventional stents in patients with VAFAs who underwent SAT.…”
Section: Discussionmentioning
confidence: 99%
“…Since the development of flow diverter stents, they have been used to redirect flow in fusiform aneurysms to achieve high occlusion rates with low rates of recurrence. However, a potential complication of flow diverter use in the posterior circulation is devastating brainstem stroke from occlusion or stenosis of a critical arterial branch ( 19 , 20 ). Our study directly compared complications and clinical and angiographic outcomes between flow diverter and conventional stents in patients with VAFAs who underwent SAT.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, reported incidence rates of DAR after FD placement ranged between 0.6 and 4% ( 9 ). The multicenter Chinese PLUS study reported an incidence of 2.1% ( 3 ). Approximately 80% of DARs occur within 30 days of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Flow diverter (FD) is an essential tool in endovascular treatment of large and giant intracranial aneurysms that can achieve satisfactory clinical and angiographic outcomes ( 2 ). However, it is associated with several complications, particularly delayed aneurysm rupture (DAR), which may cause severe neurological dysfunction or death ( 3 ). The mechanism of DAR after FD placement is not known.…”
Section: Introductionmentioning
confidence: 99%
“…This is a subgroup study of the PLUS study. 8 , 9 Three of the 14 centers were excluded because of a lack of complete angiographic imaging data. All patients with intracranial aneurysms who underwent embolization using the PED between November 2014 and October 2019 in 11 centers and who provided written informed consent for the use of any recognizable patient photographs were included.…”
Section: Methodsmentioning
confidence: 99%